2013
DOI: 10.1002/ird.1727
|View full text |Cite
|
Sign up to set email alerts
|

Saltmed Model to Simulate Yield and Dry Matter for Quinoa Crop and Soil Moisture Content Under Different Irrigation Strategies in South Italy

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
6
29
1
1
Order By: Relevance
“…The results show that the SALTMED model was able to predict dry matter and grain yield of quinoa under different irrigations conditions very well. The results obtained for total dry matter are in agreement with Hirich et al (2012) and Pulvento et al (2013) who predicted dry matter of quinoa grown in the south of Morocco and south of Italy, respectively, with the SALTMED model obtaining an R 2 of 0.98 and 0.96, respectively. Similarly, Silva et al (2013) reported …”
Section: Grain Yieldsupporting
confidence: 93%
See 1 more Smart Citation
“…The results show that the SALTMED model was able to predict dry matter and grain yield of quinoa under different irrigations conditions very well. The results obtained for total dry matter are in agreement with Hirich et al (2012) and Pulvento et al (2013) who predicted dry matter of quinoa grown in the south of Morocco and south of Italy, respectively, with the SALTMED model obtaining an R 2 of 0.98 and 0.96, respectively. Similarly, Silva et al (2013) reported …”
Section: Grain Yieldsupporting
confidence: 93%
“…The good results obtained comparing simulated SWC content with observed SWC are in agreement with those reported by Silva et al (2013) and Pulvento et al (2013) who calibrated the SALTMED model using SWC data at certain depths, using a soil moisture probe. In the calibration phase, the simulated yield and total dry matter values were very close to the measured ones (Tables IV and V).…”
Section: Calibrationsupporting
confidence: 90%
“…More recently the SALTMED model has been calibrated and validated under dry and wet year conditions using chickpea field data from Southern Portugal by (Silva et al, 2012); using saline irrigation water on quinoa (Chenopodium quinoa Willd) in Denmark (Razzaghi et al, 2011) and in Italy (Pulvento et al, 2013); and in applying deficit irrigation on quinoa, sweet corn and chickpea in Morocco (Hirich et al, 2012(Hirich et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…La quinoa ha mostrado una plasticidad para la tolerancia y/o resistencia al incremento del estrés salino y a la disminución de la disponibilidad del agua mayor que la soja 27 . La quinoa ha permitido mayores niveles de salinidad (solución salina con conductividad eléctrica máximo 52dS/m para quinoa 28 frente a 8,0dS/m para soja 29 ), ocasionando un bajo impacto en los rendimientos del grano 19,[30][31][32] , a diferencia de la significativa reducción que se ha observado en los granos de soja debido a la disminución del contenido de clorofila y de la actividad del fotosistema II 33 . El favorable comportamiento de la quinoa ha sido explicado a través de la respuesta de sus estomas al cierre y del eficiente sistema que posee para realizar ajustes osmóticos importantes para el mantenimiento de la turgencia de la hoja que la muestran insensible a las sequías y a cambios abruptos de salinidad.…”
Section: Materials Y Métodosunclassified